A study of breast cancer detection practices and beliefs in black women attending public health clinics - Duke, Suzanne S; Gordonsosby, Karen; Reynolds, Kim D; Gram, Inger T (Health Education Research, 1994)
In this study, breast cancer knowledge, beliefs and practices in low income black women were examined. First, focus groups were held with a total of 33 participants. Information gathered from the focus groups was used to develop a telephone survey which was partially based on the Health Belief Model (HBM) and administered to 92 subjects. Utilization rates of mammography and breast self-examination (BSE) were quite high; 66.3% of survey participants reported having at least one mammogram and 72.5% performed BSE. Because low-cost mammograms were available to the survey participants, these results suggest that women in this target population will utilize accessible and affordable mammograms. Several knowledge deficiencies that need to be addressed were also identified. Most of the health beliefs were not significantly associated with mammography or BSE utilization. Because the HBM has never been extensively tested on this population, its appropriateness as a behavior model for low-income women is examined. Implications for future research and interventions are discussed.
34 citations (Crossref) [2023-10-31] Place: England Duke, S S. Department of Public Health, Southern Connecticut State University, New Haven 06515, USA.
Keywords: *African Americans/px [Psychology]; *Breast Neoplasms/pc [Prevention & Control]; *Health Knowledge; Attitudes; Practice; Adult; Aged; Alabama; Blacks; Breast Neoplasms; Breast Neoplasms/eh [Ethnology]; Breast Neoplasms/px [Psychology]; Breast Self-Examination; Breast Self-Examination/px [Psychology]; Cohort Studies; Female; Human; Humans; Knowledge; Attitudes; Practice; Mammography; Mammography/px [Psychology]; Middle Age; Middle Aged; Support; U.S. Gov't; P.H.S.; adult; article; breast cancer; breast examination; cancer diagnosis; dept.hms; female; health survey; human; lowest income group; major clinical study; mammography; negro; outpatient department; priority journal; public health

Prognostic indicators for poor risk epithelial ovarian carcinoma - Rosman, Martin; Hayden, Cheryl L.; Thiel, Robert P.; Chambers, Joseph T.; Kohorn, Ernest I.; Chambers, Setsuko K.; Schwartz, Peter E. (Cancer, 1994)
Background. The objective of this study was to identify factors that categorize patients with epithelial ovarian carcinoma into favorable and unfavorable prognostic groups at the time of initial treatment. Methods. Data were analyzed from 51 women who were treated at Yale University, had an evaluable CA 125 half-life (t 0.5), and were followed for disease recurrence for at least 2 years. Results. Grade, maximum level of CA 125, and histology did not provide useful prognostic information. Stage, residual disease, minimum CA 125, and CA 125 t 0.5 individually were predictive of persistent disease or recurrence within 3 years of diagnosis with sensitivities of 97, 70, 34, and 49%, respectively, and specificities of 33, 83, 100, and 83%, respectively. When these factors are combined, defining an unfavorable prognostic group as those patients having residual disease greater than 1 cm, CA 125 t 0.5 greater than 12 days, or minimum CA 125 never falling below 35 U/ml, sensitivity and specificity were 96 and 65%, respectively, at 1 year of follow-up and 91 and 75%, respectively, at 3 years of follow-up. Conclusions. In those patients in whom residual small volume disease after primary surgery indicates a good prognosis, minimum CA 125 and CA 125 t 0.5 during chemotherapy can further categorize patients into favorable and unfavorable prognostic groups.
23 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/109-722-398-694-900
Keywords: Antigens; Tumor-Associated; Carbohydrate; CA 125 half-life tumor markers; CA 125 half‐life tumor markers; Carcinoma; Carcinoma; Endometrioid; Female; Follow-Up Studies; Forecasting; Half-Life; Human; Neoplasm Recurrence; Local; Neoplasm Staging; Ovarian Neoplasms; Prognosis; Retrospective Studies; Risk Factors; Sensitivity and Specificity; Survival Rate; article; ca 125 antigen; cancer grading; cancer recurrence; cancer size; cancer staging; dept.hms; diagnostic accuracy; disease course; epithelial ovarian cancer; female; half life time; histopathology; human; human tissue; major clinical study; ovary carcinoma; priority journal; prognosis; prognostic indicators; retrospective study